2021
DOI: 10.1111/1475-6773.13671
|View full text |Cite
|
Sign up to set email alerts
|

States' use of Medicaid to meet the needs of autistic individuals

Abstract: Objective: To assess the use of Medicaid programs, including waivers, to address the needs of aging autistic individuals. Data sources: We gathered data on Medicaid programs in place between 2004 and 2015 for 50 states and the District of Columbia from the Centers for Medicare and Medicaid Services website, by contacting state Medicaid administrators and advocacy groups, and by reviewing the Medicaid Analytic eXtract Waiver Crosswalk. Study design: This retrospective analysis classified each Medicaid program a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
12
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 11 publications
(12 citation statements)
references
References 26 publications
(28 reference statements)
0
12
0
Order By: Relevance
“…Study limitations include the potential for misclassification due to incomplete or missing claims data. Policy makers should consider bolstering continuity of waiver availability to keep autistic youths insured and connected to necessary health care services or explore other eligibility mechanisms for Medicaid …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Study limitations include the potential for misclassification due to incomplete or missing claims data. Policy makers should consider bolstering continuity of waiver availability to keep autistic youths insured and connected to necessary health care services or explore other eligibility mechanisms for Medicaid …”
Section: Discussionmentioning
confidence: 99%
“…Autistic youths are more likely than their nonautistic peers to disenroll from Medicaid as they enter adulthood due to eligibility changes and lack of appropriate Medicaid services . States can provide services through waivers that target eligibility criteria based on age and/or diagnosis for specific populations . We examined whether waivers were associated with reduced risk of Medicaid disenrollment among autistic adolescents entering adulthood.…”
Section: Introductionmentioning
confidence: 99%
“…E. Williams et al, 2017). Recent research has found that states implemented new programs to serve autistic individuals during our study years (2008–2012), but they are generally focused on children and insufficiently account for the increase in autistic youth aging into adulthood (Shea et al, 2021). Of note, autistic youth with co-occurring ID were least likely of the three groups to disenroll and most often were enrolled through the disability category of Medicaid.…”
Section: Discussionmentioning
confidence: 99%
“…Medicaid waivers are programmatic mechanisms used by states with approval from the Centers for Medicare and Medicaid Services (CMS) to provide services in homes and communities rather than institutions or other restrictive settings (Kitchener et al, 2003). More recently, ASD advocates have pushed for a parallel set of policies (Schott et al, 2021; Shea et al, 2021). Some states have created ASD-specific Medicaid programs, primarily waivers to provider home- and community-based supports to children (Velott et al, 2016), and others have opened existing supports for individuals with ID to autistic individuals (Hall-Lande et al, 2011; Rizzolo et al, 2013).…”
Section: Introductionmentioning
confidence: 99%
“…As such, the study's findings suggest numerous policy implications. First, despite the well-documented increase in reported ASD prevalence in recent decades, very few states, Ohio included, offer Medicaid waivers that are specific to ASD [ 71 ] and even fewer offer ASD-specific waivers for adults [ 72 ]. Designing ASD-specific waivers may better address caregivers' identified needs for increased availability and better access to specialized services most relevant to transition-age individuals with ASD.…”
Section: Discussionmentioning
confidence: 99%